The Notary's Responsibility for The Copy of The Deed He Made Without Evidence of Land Ownership (Case Study of The Decision of The Notary Regional Inspectorate of Daerah Khusus Ibukota Jakarta Number 07/PTS/Mj.PWN.Prov.DKIJakarta/XI/2017) - Ranty Dwiroyani (Universitas Indonesia, 2019)
A copy of the deed is a word for word copy of all deeds that are the same as the original deed or minuta deed. If there is a legal defect in the minuta deed, so is the copy of the deed. The main problem in this journal is about the validity of the copy of the deed made by the notary without any evidence of land ownership, and the notary's responsibility for the consequences of his actions. The problem occurs because in the case of decision number 07/PTS/Mj.PWN.Prov.DKIJakarta/XI/2017, evidence of land ownership in the form of an Occupatie Vergunning Letter which is the object of the deed does not exist, but the deed is still made. This research is a normative juridical research and the type of data used comes from secondary data, consisting of primary legal material and secondary legal material. Thetypology of this research is from an angle of nature including explanatory research, and data collection techniques in this study is a document study. As well as the data analysis method used is qualitative analytical. The results of this journal are deeds made without evidence of land ownership will have legal consequences, namely the deed null and void. And for these actions, the notary may be liable to civil sanctions if the party suffering from the loss demands reimbursement of costs, compensation and interest. In addition, the notary may also be subject to administrative sanctions according to the notary office and notary codes.Keywords: Copy of Deed, Evidence of Land Ownership, Occupatie Vergunning Letter.